Plant Functional Traits and Vegetation Structure Explain Pollination Networks at Scale - Kendall M. Jefferys; Luísa G. Carvalheiro; Adrian González Chaves; Jacobus Petersen; Xiongjie Deng; Waira S. Machida; Katherine C. R. Baldock; Danilo Boscolo; Daniel W. Carstensen; Alice Classen; Patrícia Alves Ferreira; Breno M. Freitas; et al. (Ecology Letters, 2026)
Quantifying biotic interactions at scale is critical to understanding ecosystem functions, such as plant‐pollinator interactions. Here, we demonstrate how woody plant functional traits and vegetation structure gathered with remote sensing can aid in predicting plant‐pollinator network indices from fine to broad spatial extents. We analysed 209 tropical plant‐pollinator networks, where vegetation characteristics were generated using spectral and LiDAR data. We found that pollination network structures were correlated to plant traits reflective of drought‐adaptive strategies and nutrient availability. Networks were predicted to be more nested and less specialised with increasing leaf nitrogen content. Further, relationships between leaf thickness, photosynthetic capacity, and water content indicate that networks may be more modular and less connected under arid, high‐light conditions where plants invest in water‐conserving tissues yet maintain high photosynthetic rates. Our findings reveal plant functional strategies as underlying environmental mechanisms that structure plant‐pollinator networks, paving the way to predict interactions using remote sensing.

Exploring climate‐related gut microbiome variation in bumble bees: An experimental and observational perspective - Fabienne Maihoff; Lukas Bofinger; Kristof Brenzinger; Alexander Keller; Alice Classen (Ecology, 2025)
Rising temperatures negatively affect bumble bee fitness directly through physiological impacts and indirectly by disrupting mutualistic interactions between bees and other organisms, which are crucial in determining species‐specific responses to climate change. Gut microbial symbionts, key regulators of host nutrition and health, may be the Achilles' heel of thermal responses in insects. They not only modulate biotic interactions with plants and pathogens but also exhibit varying thermal sensitivity themselves. Understanding how environmental changes disrupt microbiome communities is a crucial first step to determine potential consequences for host population responses. We analyzed gut bacterial communities of six bumble bee species inhabiting different climatic niches along an elevational gradient in the German Alps using 16S ribosomal DNA amplicon sequencing. We first investigated whether inter‐ and intraspecific differences in gut bacterial communities can be linked to species' elevational niches, which differ in temperature, flower resource composition, and likely pathogen pressure. A reciprocal translocation experiment between distinct climatic regions tested how the gut bacterial communities of Bombus terrestris and Bombus lucorum change short‐term when exposed to new environments. Finally, we exposed these species to heat and cold wave scenarios within climate chambers to disentangle pure temperature‐driven effects on the microbiome from other environmental effects. Interspecific variation in microbiome composition exceeded intraspecific variation. Species exhibit varying levels of gut microbiome stability, where stability is defined as the within‐group variance: lower stability, indicated by greater within‐group variance, is predominantly observed in species inhabiting higher elevations. Transplanted species showed subtle short‐term gut microbiome adjustments, marked by an increase in Lactobacillaceae upon exposure to warmer regions; however, the gut microbiomes of these bumble bees did not change under laboratory temperature scenarios. We conclude that marked differences in the gut microbiomes of bumble bees could lead to species‐specific responses to environmental change. For example, less stable microbiomes in bumble bees inhabiting higher elevations might indicate an increased sensitivity to pathogens. Short‐term microbiome changes following translocation indicate that species with relatively stable microbiomes, such as B. lucorum and B. terrestris , can rapidly integrate new bacteria, which could increase their capacity to cope with new environments under climate change.

Alpine butterflies want to fly high: Species and communities shift upwards faster than their host plants - Janika M. Kerner; Jochen Krauss; Fabienne Maihoff; Lukas Bofinger; Alice Classen (Ecology, 2023)
Despite sometimes strong codependencies of insect herbivores and plants, the responses of individual taxa to accelerating climate change are typically studied in isolation. For this reason, biotic interactions that potentially limit species in tracking their preferred climatic niches are ignored. Here, we chose butterflies as a prominent representative of herbivorous insects to investigate the impacts of temperature changes and their larval host plant distributions along a 1.4‐km elevational gradient in the German Alps. Following a sampling protocol of 2009, we revisited 33 grassland plots in 2019 over an entire growing season. We quantified changes in butterfly abundance and richness by repeated transect walks on each plot and disentangled the direct and indirect effects of locally assessed temperature, site management, and larval and adult food resource availability on these patterns. Additionally, we determined elevational range shifts of butterflies and host plants at both the community and species level. Comparing the two sampled years (2009 and 2019), we found a severe decline in butterfly abundance and a clear upward shift of butterflies along the elevational gradient. We detected shifts in the peak of species richness, community composition, and at the species level, whereby mountainous species shifted particularly strongly. In contrast, host plants showed barely any change, neither in connection with species richness nor individual species shifts. Further, temperature and host plant richness were the main drivers of butterfly richness, with change in temperature best explaining the change in richness over time. We concluded that host plants were not yet hindering butterfly species and communities from shifting upwards. However, the mismatch between butterfly and host plant shifts might become a problem for this very close plant–herbivore relationship, especially toward higher elevations, if butterflies fail to adapt to new host plants. Further, our results support the value of conserving traditional extensive pasture use as a promoter of host plant and, hence, butterfly richness.

Contrasting patterns of richness, abundance, and turnover in mountain bumble bees and their floral hosts - Douglas B. Sponsler; Fabrice Requier; Katharina Kallnik; Alice Classen; Fabienne Maihoff; Johanna Sieger; Ingolf Steffan‐Dewenter (Ecology, 2022)
Environmental gradients generate and maintain biodiversity on Earth. Mountain slopes are among the most pronounced terrestrial environmental gradients, and the elevational structure of species and their interactions can provide unique insight into the processes that govern community assembly and function in mountain ecosystems. We recorded bumble bee–flower interactions over 3 years along a 1400‐m elevational gradient in the German Alps. Using nonlinear modeling techniques, we analyzed elevational patterns at the levels of abundance, species richness, species β ‐diversity, and interaction β ‐diversity. Though floral richness exhibited a midelevation peak, bumble bee richness increased with elevation before leveling off at the highest sites, demonstrating the exceptional adaptation of these bees to cold temperatures and short growing seasons. In terms of abundance, though, bumble bees exhibited divergent species‐level responses to elevation, with a clear separation between species preferring low versus high elevations. Overall interaction β ‐diversity was mainly caused by strong turnover in the floral community, which exhibited a well‐defined threshold of β ‐diversity rate at the tree line ecotone. Interaction β ‐diversity increased sharply at the upper extreme of the elevation gradient (1800–2000 m), an interval over which we also saw steep decline in floral richness and abundance. Turnover of bumble bees along the elevation gradient was modest, with the highest rate of β ‐diversity occurring over the interval from low‐ to mid‐elevation sites. The contrast between the relative robustness bumble bee communities and sensitivity of plant communities to the elevational gradient in our study suggests that the strongest effects of climate change on mountain bumble bees may be indirect effects mediated by the responses of their floral hosts, though bumble bee species that specialize in high‐elevation habitats may also experience significant direct effects of warming.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Increasing the phylogenetic coverage for understanding broad-scale diversity gradients - Marcell K. Peters; Alice Classen; Jörg Müller; Ingolf Steffan-Dewenter (Oecologia, 2020)
Despite decades of scientific effort, there is still no consensus on the determinants of broad-scale gradients of animal diversity. We argue that general drivers of diversity are unlikely to be found among the narrowly defined taxa which are typically analyzed in studies of broad-scale diversity gradients because ecological niches evolve largely conservatively. This causes constraints in the use of available niche space leading to systematic differences in diversity gradients among taxa. We instead advocate studies of phylogenetically diverse animal communities along broad environmental gradients. Such multi-taxa communities are less constrained in resource use and diversification and may be better targets for testing major classical hypotheses on diversity gradients. Besides increasing the spatial scale in analyses, expanding the phylogenetic coverage may be a second way to achieve higher levels of generality in studies of broad-scale diversity gradients.

Temperature versus resource constraints: which factors determine bee diversity on M ount K ilimanjaro, T anzania? - Alice Classen; Marcell K. Peters; William J. Kindeketa; Tim Appelhans; Connal D. Eardley; Mary W. Gikungu; Andreas Hemp; Thomas Nauss; Ingolf Steffan‐Dewenter (Global Ecology and Biogeography, 2015)
Aim Understanding the mechanisms controlling variation in species richness along environmental gradients is one of the most important objectives in ecology. Resource availability is often considered as the major driver of animal diversity. However, in ectotherms, temperature might play a predominant role as it modulates metabolic rates and the access of animals to resources. Here, we investigate the relative importance of resource availability and temperature in determining the diversity pattern of bees along a 3.6‐km elevational gradient. Location M ount K ilimanjaro, T anzania. Methods We assessed bee species richness and abundance with pan traps and floral resources with transect records on 60 study sites which were equally distributed over six near‐natural and six disturbed habitat types along an elevational gradient from 870 to 4550 m a.s.l. We used path analysis to disentangle the effects of temperature, precipitation, floral resource abundance, bee abundance and land use on bee species richness. In addition, we monitored flower visitation rates during transect walks at different elevations to evaluate the temperature dependence of bee–flower interactions. Results Bee species richness continuously declined with elevation in natural and disturbed habitats. While the abundance of floral resources had a significant but only weak effect on species richness, the effect of temperature was strong. Temperature had a strong positive effect on species richness that was not mediated by bee abundance and an indirect effect via bee abundances. We observed higher levels of bee–flower interactions at higher temperatures, supporting the hypothesis that temperature limits diversity by constraining resource exploitation in ectotherms. Main conclusions Temperature and the availability of resources shape species richness patterns along environmental gradients. In ectothermic organisms like bees temperature seems to have the more important role, as it both limits the access to resources (abundance‐mediated effect) and accelerates other (abundance‐independent) ecological and evolutionary processes that drive the maintenance and origination of diversity.